Molecular insight into genetic differentiation, population structure and banding pattern analysis of Bambara groundnut (Vigna subterranea L. Verdc.) linked with inter simple sequence repeats (ISSR) - Khan, Md Mahmudul Hasan; Rafii, Mohd Y.; Ramlee, Shairul Izan; Jusoh, Mashitah; Al Mamun, Md; Kundu, Bimal Chandra (Springer Nature, 2023)
Background: A set of 44 selected Bambara groundnut (Vigna subterranea L. Verdc.) accessions was sampled from 11 distinct populations of four geographical zones to assess the genetic drift, population structure, phylogenetic relationship, and genetic differentiation linked with ISSR primers. Methods and results: The amplification of genomic DNA with 32 ISSR markers detected an average of 97.64% polymorphism while 35.15% and 51.08% polymorphism per population and geographical zone, respectively. Analysis of molecular variance revealed significant variation within population 75% and between population 25% whereas within region 84% and between region 16%. The Bidillali exposed greater number of locally common band i.e., NLCB (≤ 25%) = 25 and NLCB (≤ 50%) = 115 were shown by Cancaraki while the lowest was recorded as NLCB (≤ 25%) = 6 and NLCB (≤ 50%) = 72 for Roko and Maibergo, accordingly. The highest PhiPT value was noted between Roko and Katawa (0.405*) whereas Nei’s genetic distance was maximum between Roko and Karu (0.124). Based on Nei’s genetic distance, a radial phylogenetic tree was constructed that assembled the entire accessions into 3 major clusters for further confirmation unrooted NJ vs NNet split tree analysis based on uncorrected P distance exposed the similar result. Principal coordinate analysis showed variation as PC1 (15.04%) > PC2 (5.81%). Conclusions: The current study leads to prompting the genetic improvement and future breeding program by maximum utilization and better conservation of existing accessions. The accessions under Cancaraki and Jatau are population documented for future breeding program due to their higher genetic divergence and homozygosity.